Liraglutide, GLP-1 receptor agonist, for chronic weight loss. Issue 5 (2nd September 2016) - Moore, Katherine G.; Shealy, Kayce; Clements, Jennifer N.
ABSTRACT: Introduction : Since 1990, the prevalence of obesity has been steadily increasing in the United States. Over the past four years, new medications have become approved and available, allowing for more options in the management of chronic weight loss among overweight or obese patients. This review article summarizes the efficacy, safety, and clinical attributes of liraglutide among overweight or obese patients with or without comorbidities. Areas covered : A MEDLINE search, from 1970 to June 2016, was conducted using key terms—glucagon-like peptide-1 receptor agonist, liraglutide, overweight, and obesity. Published clinical trials, in the English-language and with primary endpoints related to weight loss, were reviewed and critiqued in this article. Expert commentary : Available as a subcutaneous daily injection, liraglutide is the first glucagon-like peptide-1 (GLP-1) receptor agonist indicated for obesity management, as adjunct therapy with lifestyle and behavioral modifications. Liraglutide 3 mg daily has been associated with greater weight loss than placebo or orlistat in patients without type 2 diabetes. Additionally, liraglutide has resulted in reductions in waist circumference, systolic and diastolic blood pressure, and improvements in lipid panel among overweight and obese patients with and without type 2 diabetes.